STUDENTS’ PERCEPTION TOWARD TEACHING ENGLISH VOCABULARY THROUGH TOTAL PHYSICAL RESPONSE (TPR) METHOD - Ibrohim, Achmad Taufiq; Septianti, Astri; Sadikin, Irma Savitri (IKIP Siliwangi, 2018)
The objective of the research is to investigate the students’ perception on teaching english vocabulary through Total Physical Response (TPR) technique and to identify the benefits that the students obtained from that technique. This research used a qualitative descriptive research method. The respondents of the research were eight grade students of SMPN 2 Plered Purwakarta. The data were obtained from questionaire and interview. The results of the study that the teaching english vocabulary through Total Physical Response (TPR) technique could help students’ vocabulary in learning english. Based on interview and questionnaire, they showed some improvement on process of get new vocabulary from learning with that technique. Moreover, the data from questionaire and interview showed that there were some benefits of TPR method: 1. Developt of students’ speaking ability and increasing vocabulary, 2. Increasing the students participation in the class, 3. Having a fun learning atmosphere.